Evaluation of Women’s Knowledge about Risk Factors and Early Detection of Breast Cancer among Women Working in Governmental Sector in Gaza Strip, Palestine - Hassouna, Eman Suliman (Journal of medical and pharmaceutical sciences, 2025)
Background: Breast cancer (BC) is the most common prevailing type of women cancer and is the second cause of cancer-related mortality in women. Purpose: The purpose of the study was to evaluate women's knowledge about signs and symptoms, risk factors and early detection of breast cancer at governmental sector in Gaza Strip. Materials & Methods: The study utilized a cross-sectional design. The sample included 253 women employed in the ministries in Gaza Strip. Data were collected through a pre-tested self-administered questionnaire. The study was conducted during the period from January to June 2023. Results: The results showed that 47.4% of the study participants aged between 31 – 40 years, and 54.9% have bachelor degree. Regarding knowledge about importance of early detection of breast cancer, 59.7% of the study participants have good knowledge, 38.3% have moderate knowledge, and 2% have low knowledge. In addition, 27.3% know that change in breast shape and size, painless breast mass, armpit node, abnormal secretions from the nipple, and thickness of breast were among symptoms of BC. Concerning risk factors, 71.2% of women stated that increasing of age will increase the possibility of developing BC, 59.3% reported that absence of pregnancy and childbirth increase the possibility of developing BC.There were no significant association between knowledge about breast cancer with age (p-value 0.800), marital status (p-value 0.221), and level of education (p-value 0.742). Conclusion: The study concluded that women at governmental sector need more experience in dealing with breast cancer.
Keywords: Women’s knowledge; Risk factors; Screening and early detection; Breast cancer; Gaza Strip